BALAI ADAT SEBAGAI IDENTITAS PERSUKUAN MELAYU BAWI DI KENEGERIAN KUOK - Resdati Resdati (LPPM Institut Pendidikan Nusantara Global, 2023)
This research was conducted in Empat Balai Village, Kuok District with the aim of knowing the history, culture and identity of the Bawi Malay Tribe in Kenegerian Kuok. This study used a descriptive qualitative method with data collection techniques in the form of observation, documentation and direct interviews with several research subjects who knew about the history and culture of the Bawi Malay ethnic group in Kenegerian Kuok. The traditional hall of the Bawi Malay Tribe is located in Kebuh Tengah Hamlet, Empat Balai Village. The traditional hall has a symbol in the form of a lion statue which symbolizes the tribe. The head of the Malay Bawi tribe is called Datuok Singo, according to his title lion which symbolizes strength and intelligence. The Bawi Malay Tribal customary hall functions as a place for deliberation and consensus to find solutions to any existing problems. The adat hall also functions as a gathering place for relatives and nephews from the Bawi Malay ethnic group, both those outside the city and abroad, such as the halal bihalal event. The purpose of holding the event is to strengthen the bonds of brotherhood among the Bawi Malay people. Therefore, the entire Bawi Malay ethnic community must contribute and participate so that the adat hall can function properly and remain sustainable as a form of cultural identity.